2012
DOI: 10.1016/j.chembiol.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating Signaling Nodes Involved in Cellular Transformations Using Kinase Activity Probes

Abstract: Summary Protein kinases catalyze protein phosphorylation and thereby control the flow of information through signaling cascades. Currently available methods for concomitant assessment of the enzymatic activities of multiple kinases in complex biological samples rely upon indirect proxies for enzymatic activity, such as posttranslational modifications to protein kinases. Our laboratories have recently described a method for directly quantifying the enzymatic activity of kinases in unfractionated cell lysates us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…66 Based on this scaffold approach and the benefits of the C-Sox amino acid, further sensors for specific kinases (p38, JNK, MAPK family) have been developed, providing insight into the modulation of kinase activities in diseased tissue samples. 67 Chelating FlAAs have found use in other applications as well. For example, Wang and coworkers have reported the synthesis and incorporation of the metal-chelating 2-amino-3-hydroxyquinoline-3-yl)-propanoic acid (HQ-Ala) into proteins not only as a CHEF fluorescent reporter, but also a handle for introduction of a heavy metal ion for Xray crystallography phasing.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…66 Based on this scaffold approach and the benefits of the C-Sox amino acid, further sensors for specific kinases (p38, JNK, MAPK family) have been developed, providing insight into the modulation of kinase activities in diseased tissue samples. 67 Chelating FlAAs have found use in other applications as well. For example, Wang and coworkers have reported the synthesis and incorporation of the metal-chelating 2-amino-3-hydroxyquinoline-3-yl)-propanoic acid (HQ-Ala) into proteins not only as a CHEF fluorescent reporter, but also a handle for introduction of a heavy metal ion for Xray crystallography phasing.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…Consensus phosphorylation sites often do not provide adequate selectivity amongst endogenous kinases; well-characterized substrates should be employed when possible. As a general guideline, we have found that peptide substrates with k cat values of >20 min −1 provide a sufficient turnover in order to visualize endogenous kinase activity in cell lysates within one hour (Stains et al, 2012). In addition, K M values in the low μM range (<5 μM) typically provide selectivity for the KOI while minimizing off-target activity if appropriate sensor concentrations are used (i.e.…”
Section: Strategic Planningmentioning
confidence: 99%
“…There are two situations that can arise in which obtained data may not produce a hyperbolic plot. First, the data may exhibit an initial lag phase prior to the linear region of the data that should be used for work-up (Lukovic et al, 2009; Shults et al, 2005; Stains et al, 2011; Stains et al, 2012). In this case, the initial lag phase should not be included in the analysis as this will bias the fit.…”
Section: Basic Protocol 1: General Cell Lysate Assay Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…They often malfunction in disease states, such as cancer. Through interactions with colleagues at both MIT and other universities, Imperiali and her team fine-tuned the approach into a method that can screen kinase inhibitors and profile kinase activities in cell and tissue lysates (7,8). "The approach that we developed has been commercialized, and we are now looking towards ways to further development of the methods for diagnostic applications," she says.…”
Section: Measuring and Manipulating Biochemical Processesmentioning
confidence: 99%